Comparative Efficacy of Third and Fourth-Generation Cephalosporins against Escherichia coli and Klebsiella pneumoniae Isolates from Recurrent Urinary Tract Infections in Al-Najaf Province - Al-Mayali, Enas Jalil Baqer; Almahbobi, Taghreed F. (Central Asian Journal of Medical and Natural Science, 2025)
Urinary Tract Infection (UTI) Urinary tract infections are among the most common infections worldwide. They are most often caused by bacteria entering the urethra from the skin or rectum. The most common bacterial causes of UTIs worldwide are Escherichia coli and Klebsiella pneumoniae, and women and the elderly are most affected. In recent years, these two bacteria have become more resistant to traditional antibiotics due to the production of enzymes ESBL that make them difficult to treat. This study included two main axes, the first was the isolation of Escherichia coli and Klebsiella pneumoniae from the urine of patients suffering from recurrent urinary tract infections, the second axis includes a study of the effect of the cephalosporin group commonly used in hospitals to treat urinary tract infections. Within the framework of this study, (31) isolates of Escherichia coli and (17) isolates of Klebsiella pneumoniae were isolated from a group of patients with recurrent urinary tract infections. After conducting a sensitivity test for the isolates in this study using a group of generations of Cephalosporin, which are widely used in hospitals, they showed high resistance to most generations. E. coli showed high resistance to ceftriaxone at a rate of 93.5%, followed by Cefepime 87.1%, Cefdinir 74.2%, Cefixime 64.5%. While Klebsiella pneumoniae gave higher resistance to cefixime 88%, followed by Cefdinir 87.5%, Ceftriaxone 87.5%, Cefepime 76.4%. Therefore, caution should be exercised when using these treatments excessively, especially in cases of recurrent infections and the use of alternative treatments to reduce resistance.